Basics of Wood Materials and Woodworking Technology - Tursunboy Axmedov; Siddikova Ranoxon Abdulxay qizi; Xusanova Lobarxon Murodovna (Zien Journals, 2022)
This article describes the rules of wood production, wood production technology, wood used in wood production, their properties, wood materials, technical safety rules for manual processing of wood on a carpentry machine.
Keywords: arches; beams stropil; sinch sarrob; spruce